Evaluating cis‐2, 6‐Dimethylpiperidide (cis‐DMP) as a Base Component in Lithium‐Mediated Zincation Chemistry. Issue 40 (19th August 2013) - Armstrong, David R.; Garden, Jennifer A.; Kennedy, Alan R.; Leenhouts, Sarah M.; Mulvey, Robert E.; O'Keefe, Philip; O'Hara, Charles T.; Steven, Alan
Abstract Most recent advances in metallation chemistry have centred on the bulky secondary amide 2, 2, 6, 6‐tetramethylpiperidide (TMP) within mixed metal, often ate, compositions. However, the precursor amine TMP(H) is rather expensive so a cheaper substitute would be welcome. Thus this study was aimed towards developing cheaper non‐TMP based mixed‐metal bases and, as cis‐2, 6‐dimethylpiperidide (cis‐DMP) was chosen as the alternative amide, developing cis‐DMP zincate chemistry which has received meagre attention compared to that of its methyl‐rich counterpart TMP. A new lithium diethylzincate, [(TMEDA)LiZn(cis‐DMP)Et2] (TMEDA=N, N, N′, N′‐tetramethylethylenediamine) has been synthesised by co‐complexation of Li(cis‐DMP), Et2Zn and TMEDA, and characterised by NMR (including DOSY) spectroscopy and X‐ray crystallography, which revealed a dinuclear contact ion pair arrangement. By using N, N‐diisopropylbenzamide as a test aromatic substrate, the deprotonative reactivity of [(TMEDA)LiZn(cis‐DMP)Et2] has been probed and contrasted with that of the known but previously uninvestigated di‐tert‐butylzincate, [(TMEDA)LiZn(cis‐DMP)tBu2]. The former was found to be the superior base (for example, producing the ortho‐deuteriated product in respective yields of 78 % and 48 % following D2O quenching of zincated benzamide intermediates). An 88 % yield of 2‐iodo‐N, N‐diisopropylbenzamide was obtained on reaction of two equivalents of the diethylzincate with the benzamide followed by iodination. Comparisons are also drawn using 1, 1, 1, 3, 3, 3‐hexamethyldisilazide (HMDS), diisopropylamide and TMP as the amide component in the lithium amide, Et2Zn and TMEDA system. Under certain conditions, the cis‐DMP base system was found to give improved results in comparison to HMDS and diisopropylamide (DA), and comparable results to a TMP system. Two novel complexes isolated from reactions of the di‐tert‐butylzincate and crystallographically characterised, namely the pre‐metallation complex [{(iPr)2N(Ph)CO}LiZn(cis‐DMP)tBu2] and the post‐metallation complex [(TMEDA)Li(cis‐DMP){2‐[1‐C(=O)N(iPr)2]C6H4}Zn(tBu)], shed valuable light on the structures and mechanisms involved in these alkali‐metal‐mediated zincation reactions. Aspects of these reactions are also modelled by DFT calculations.